La nueva humanización del agua : una lectura desde el ambientalismo inclusivo - Faccendini, Aníbal Ignacio (UNR Editora ; CLACSO, 2019)
What if we argued that -far from the widespread stigmatization that associates youth from popular sectors with crime- a large number of young people from communities hit by social violence and the absence of public policies dedicate their days to caring for other young people? The work of Yicel Giraldo Giraldo and Alexander Ruiz Silva studies solidarity as the axis and motor of youth social organizations dedicated to caring for their peers, testing an interpretation of the ethical and political bets that young people from the communes of Medellín deploy to face adverse situations marked by pain and suffering. Through 32 youth life stories, Solidarity proposes to reconstruct the complex network of solidarity initiatives and actions promoted by the youth of the Medellín communes. Music, audiovisuals, dance, graffiti art and the defense of the environment are platforms from which young people summon others, affect them, move them, summon them to form a community.